Yam systems: Australia-IITA learning exchange for food security - Prof. Yasmina Sultanbawa - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
A four-member team led by Professor Yasmina Sultanbawa from the University of Queensland, Australia, visited the International Institute of Tropical Agriculture (IITA) as part of a collaborative engagement with the institute’s Yam Breeding Program. The visit aimed to deepen their understanding of yam research and explore strategies to enhance yam production within their home communities.